Políticas públicas de educação e informação para inclusão e acessibilidade: estudo realizado entre usuários com deficiência na Biblioteca do Instituto Federal da Paraíba - Campus Cabedelo - Pereira, Rodrigo Araújo de Sá (2018)
This research deals with a study on the application of public policies of education and information for people with disabilities. It seeks to clarify the following question: How has the library of the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Campus Cabedelo been acting with the execution of policies, programs, projects and general public practices of education for people with disabilities? The theoretical framework briefly explains Brazilian legislations, resolutions and norms regarding accessibility. It also brings the concept of information and analyzes if the servers of that library are prepared to serve this public and if that user is satisfied with the service offered. The objective of the study is to investigate the implementation of public education and information policies in the library of the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Campus Cabedelo, aiming to understand the perspectives of inclusion and information accessibility for people with disabilities. and as objectives specific: a) to discuss the construction and execution of public education and information policies applied to libraries; b) verify how the service is offered to users with disabilities; and c) to propose strategies for the application of policies, programs and projects of the library of the Instituto Federal de Educação, Ciência e Tecnologia da Paraíba - Campus Cabedelo for inclusion and accessibility for people with disabilities. For this, the methodology used is characterized by descriptive, bibliographic and documentary aspects, besides making a case study. There is collection and analysis of data through a mixed questionnaire with users with disabilities and the treatment of this data will occur in quantitative and qualitative forms. It seeks to understand the exclusion and inclusion of people with disabilities in society with a brief history. Finally, recommendations will be made to improve the service offered by the Library.